Human capital, pollution control, and endogenous growth - Birgit Kirschbaum; Susanne Soretz (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
We analyse an endogenous growth model with pollution and abatement. Human capital is used in the production sector as well as in pollution control. We show that greener preferences may increase the pollution level, driven by the decrease in human capital intensity in the production sector and the human capital reallocation. This can help to explain why environmental quality in emerging countries frequently deteriorates.
Keywords: O1; O4; Q2; Q5; 330